Year-round presence of high levels of plasma antifreeze peptides in a temperate fish, ocean pout ( Macrozoarces americanus ) - Fletcher, Garth L.; Hew, Choy L.; Li, Xiaomao; Haya, Katsuji; Kao, Ming H. (Canadian Journal of Zoology, 1985)
The annual cycle of plasma antifreeze activity and Na + and Cl − concentrations were measured in Newfoundland and New Brunswick ocean pout (Macrozoarces americanus) maintained in the laboratory under Newfoundland conditions of water temperature and photoperiod. The Na + and Cl − concentrations and antifreeze activity showed distinct seasonal cycles in both groups of fish, with the highest values occurring during the winter. Relatively high concentrations of antifreeze peptides were present in the Newfoundland ocean pout at all times of the year. Antifreeze peptides were also present in the New Brunswick fish throughout the year; however, the concentrations found were approximately one-tenth of those observed in Newfoundland fish. A comparison of the antifreeze peptides from summer and winter samples from Newfoundland ocean pout and winter samples from New Brunswick ocean pout using high performance liquid chromatography revealed essentially identical elution profiles.